2021
DOI: 10.1016/j.esmoop.2021.100260
|View full text |Cite
|
Sign up to set email alerts
|

Targeting HER2 in non-small-cell lung cancer (NSCLC): a glimpse of hope? An updated review on therapeutic strategies in NSCLC harbouring HER2 alterations

Abstract: Non-small-cell lung cancer (NSCLC) harbouring HER2 alterations is now considered a distinct molecular subtype. The activation of HER2 in NSCLC occurs via three mechanisms, i.e. gene mutation (1%-4% of cases), gene amplification (2%-5%) and protein overexpression (2%-30%), with different prognostic and predictive outcomes. So far, non-selective tyrosine kinase inhibitors (TKIs) have shown a minor benefit in H ER 2 -mutant NSCLC patients with objective response ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
92
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(93 citation statements)
references
References 90 publications
(258 reference statements)
0
92
0
1
Order By: Relevance
“…Our results suggest an inner association between the MIP aggressive phenotype and neurogenesis. The activation of well-known proto-oncogene ERBB2 signaling was associated with poor outcomes in NSCLC ( 34 ), coinciding with MIP characteristics. The copy number of genes related to the immune system, innate immune system, interleukin signaling, SHC1 events, ERK activation, and FRS-mediated signaling were also found to decrease in MIP.…”
Section: Discussionmentioning
confidence: 99%
“…Our results suggest an inner association between the MIP aggressive phenotype and neurogenesis. The activation of well-known proto-oncogene ERBB2 signaling was associated with poor outcomes in NSCLC ( 34 ), coinciding with MIP characteristics. The copy number of genes related to the immune system, innate immune system, interleukin signaling, SHC1 events, ERK activation, and FRS-mediated signaling were also found to decrease in MIP.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the DrugBank analysis showed that the drug targeting GAA was Trastuzumab-deruxtecan. Trastuzumab-deruxtecan is primarily used for patients with human epidermal growth factor receptor 2 (HER2)-mutant tumours including non-SCLC and in the absence of SCLC (79)(80)(81). Upon binding to HER2, Trastuzumab-deruxtecan disrupts the HER2 signalling, undergoes internalisation and intracellular linker cleavage by lysosomal enzymes and ultimately causes DNA damage and apoptotic cell death (80).…”
Section: Discussionmentioning
confidence: 99%
“…Human epidermal growth factor receptor 2 (HER2) is well known as the target in many cancer treatments. HER2-targeted therapy is established as the standard treatment for breast cancer and gastric adenocarcinoma [ 46 , 47 ], and it is recently being investigated for other solid tumors such as non-small cell lung cancer and colorectal cancer [ 48 , 49 ]. Overexpression of HER2 is observed in approximately 30% of osteosarcoma cases and was suggested to be poor-prognosis factor [ 50 , 51 ], and thus HER2 could be a candidate for the targeted therapy of osteosarcoma.…”
Section: Osteosarcomamentioning
confidence: 99%